Pelaksanaan Pembelajaran Pendidikan Agama Islam (PAI) Berbasis Merdeka Belajar di MAN 2 Palembang - Rahma Tri Utami; Ahmad Zainuri (PAI RAFAH, 2024)
This article discusses the implementation of Islamic Religious Education (PAI) learning based on the Merdeka Curriculum at MAN 2 Palembang. This research uses a qualitative descriptive method to describe the implementation of the curriculum and its impact on students. The results showed that the implementation of Merdeka Belajar Curriculum has provided a more enjoyable learning experience and enabled students to develop their talents and interests. Supporting factors such as student motivation, school support, and parental involvement play an important role in the success of this curriculum. However, there are some challenges, including policy adjustments that change frequently and differences in students' ability to understand the material. Overall, the program has been successful in improving the teaching and learning process although it still needs attention to the barriers that exist.